Implementing a pharmacovigilance program to evaluate cutaneous adverse drug reactions in an antiretroviral access program - Mudzviti, Tinashe (2012)
BACKGROUND: Cutaneous adverse drug reactions (cADRs) can cause significant morbidity and distress in patients especially in the HIV infected population on antiretroviral therapy. Adverse Drug Reaction monitoring and ascertaining causality in resource limited settings still remains a challenge. This study was carried out to evaluate causality and measure incidence of cADRs in HIV infected patients on highly active antiretroviral therapy. The study was also designed to test a 3-step approach in the monitoring and evaluation of ADRs in resource limited settings. METHODOLOGY: A retrospective patient medical records review was carried out at the Parirenyatwa Family Care Centre, (Harare, Zimbabwe). Cases of cADRs were reported to the Medicines Control Authority of Zimbabwe (Drug regulating body in Zimbabwe) for assessment and causality classification. RESULTS: Two hundred and twenty-one patient records were randomly selected and reviewed to determine if any diagnosis of cADRs was made by clinicians. Causality assessment revealed 13.1% of cADRs which were due to an offending agent in the antiretroviral therapy against an initial incidence of 17.6% which had been determined by the physicians. CONCLUSIONS: cADRs had an incidence of 13.1% within the population under study due to non nucleoside reverse transcriptase inhibitors (NNRTIs). Most reactions were due to the NNRTIs which contributed 72.4 % of all cADRs. A panel of experts from the drug regulatory authority can be used as an implementation based mechanism in ascertaining causality objectively in settings where resources are constrained.